ANALISIS MANAJEMEN PERSEDIAAN BAHAN BAKU COKELAT PADA INDUSTRI RAPOVIAKA SIMPLE DI KOTA PALU - fitra. H, Nur Azmi; Effendy, Effendy; Howara, Dafina (AGROTEKBIS, 2017)
The aim of research are to find out the amount of economical order EOQ (Economy Order Quantity), the time lengthand the amount of order at Industry Rapoviaka simple st. Lasoso No. 45 Sub District Palu West of Palu City on April until 2016. The source of the data from Rapoviaka simple industry. The analytical tool used in this research is theAnalysis of EOQ (Economic Order Quantity), Safety stock, ROP (Re-Order Point). Result from this study is that the number of the purchasing material at the most economical shoulder simple Rapoviaka industry with an average that is equel to 17,826 kg, for the month of 16,67 kg November, December amounted to 16,76 kg, January 18,56, February 18,54 kg, and March 18,60 kg, with a frequncy of 3 times the message ordering in a mounth, safety stock of raw material requirements per production in Novemeber     and December of 4,17 kg, for mounth January, February and March requirements per production 5,00 kg. to reorder point in November and December of 8,33 kg and in January, February, March, amounting 10,00 kg. The total cost of materials inventory shoulder simple Rapoviaka Industry average of Rp.191.295,73/mounth. Key Words : Chocolate, management, material inventory.